Imprints of Prayer in Memory: Lyrical Subject’s Experience in the Poetry of Alfonsas Nyka-Niliūnas and Czesław Miłosz - Jakaitė, Dalia (Colloquia, 2022)
Critics, who analyze the religiosity inherent in Czesław Miłosz’s poetry, quite often link it to the writer’s attitude to history and the experience of time (M. Masłowski and others). They also draw attention to the poetic transformation of prayers. However, the place of prayer in the consciousness of memory and other forms of this interaction have not been investigated in detail, especially not by Lithuanians. A new direction of comparison, i.e. the interactions of prayer and memory in the poetry of Miłosz and Alfonsas Nyka-Niliūnas, determines the novelty of the study. Lithuanian critics (V. Skrupskelytė, etc.) have analyzed religious experiences and the alterations of the Bible in the poetry of Nyka-Niliūnas, also hinting at prayer; however, the memory of prayer as a phenomenon deserves a closer look. Considering prayer as one of the essential religious phenomena, the main object of the article concerns the forms of interaction between the lyrical subject’s prayer and memory, analyzed with the help of literary theology and phenomenology.
Keywords: memory; prayer; poetry; subject; Alfonsas Nyka-Niliūnas; Czesław Miłosz